A versatile embedding medium for freeform bioprinting with multi-crosslinking methods. (1st July 2022) - Li, Qi; Jiang, Zhuoran; Ma, Liang; Yin, Jun; Gao, Ziqi; Shen, Luqi; Yang, Huayong; Cui, Zhanfeng; Ye, Hua; Zhou, Hongzhao
Abstract: Embedded freeform writing addresses the contradiction between the material printability and biocompatibility for conventional extrusion-based bioprinting. However, the existing embedding mediums have limitations concerning the restricted printing temperature window, compatibility with bioinks or crosslinkers, and difficulties on medium removal. This work demonstrates a new embedding medium to meet the above demands, which composes of hydrophobically modified hydroxypropylmethyl cellulose and Pluronic F-127. The adjustable hydrophobic and hydrophilic associations between the components permit tunable thermoresponsive rheological properties, providing a programmable printing window. These associations are hardly compromised by additives without strong hydrophilic groups, which means it is compatible with the majority of bioink choices. We use polyethylene glycol 400, a strong hydrophilic polymer, to facilitate easy medium removal. The proposed medium enables freeform writing of the millimetric complex tubular structures with great shape fidelity and cell viability. Moreover, five bioinks with up to five different crosslinking methods are patterned into arbitrary geometries in one single medium, demonstrating its potential in heterogeneous tissue regeneration. Utilizing the rheological properties of the medium, an enhanced adhesion writing method is developed to optimize the structure's strand-to-strand adhesion. In summary, this versatile embedding medium provides excellent compatibility with multi-crosslinking methods and a tunable printing window, opening new opportunities for heterogeneous tissue regeneration.